FRAMING ANALYSIS OF SEXUAL VIOLENCE REPORTING IN NU ONLINE MEDIA AND SUARA MUHAMMADIYAH - Sahawi, Ridy Sulhana; Sujoko, Anang; Wulandari , Maulina Pia (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2023)
This research aims to discuss framing analyses of sexual violence in NU and Suara Muhammadiyah online media. This research uses a qualitative research method with Robert Etnman's framing analysis approach. Robert Etnman's framing analysis method is used to see how a media constructs reality and to see that news is understood and framed before being presented to the public with four elements, namely: define problems, diagnose causes, make moral judgments, and make treatment recommendations. Based on the results of the analysis using four elements of framing by Robert Etnman, the framing carried out by online media NU and Suara Muhammadiyah regarding reporting on sexual violence explains the causes, effects, triggers, and handling of sexual violence. The online media NU and Suara Muhammadiyah framed the news by looking for informants who could provide a number of facts and testimonies regarding sexual violence. NU online news framing emphasizes that sexual violence is an evil intention that is contrary to religion, morals, and education, which must be opposed and prevented. Suara Muhammadiyah's news framing emphasizes Islamic teachings that sexual violence has harmed Islamic educational institutions, which prioritize compassion.